Effect of local sand ratio toward compressive strength and dielectric properties of concrete. (July 2020) - Mufti, N; Yohana, K; Fuad, A; Taufiq, A; Sunaryono, S
Abstract: In this work, we report the effect of local sand ratio on compressive strength and dielectric properties of concrete. Concretes were made by mixing Portland cement mixed with local sand in various compositions of 1:2, 1:3.1:4.1:5, 1:6, and 1:7. These mixtures were printed in the form of 5×5×5 cm 3 and have maintained (soaked) for 27 days. Specimens were characterized on the 28th day. Compressive strength was tested using the compression test and dielectric test with a series LCR meter. The compressive strength test results show that the more significant sand addition in the mixture decreases the compressive strength. Dielectric test results reveal that the higher addition of sand in the mixture reduces the dielectric constant. These results indicate that the dielectric constant measurement can be used as an alternative method for the investigation of concrete quality.